Karakteristik Pembakaran Biobriket Batubara Campuran Batubara dan Ampas Tebu - Rr. Harminuke Eko Handayani; RR. Yunita Bayu Ningsih; Canda Muammal (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2017)
Coal is a kind of energy that really close to thermal properties. Low rank coal in Indonesia is hardly tobe used as a raw coal. The making of biobatubara briquette is one of a thing people managed to uselow rank coal. In this research talk about the influence of the pressure in making biobatubara briquetteto know the burning characteristic. The analysis is done by using Thermogravimetric Analyzer. Thepressure that used is 75, 100, 125 and150, in kg/cm2 units. The result of this research showed thattemperature of ITVM between 263-269 ºC , ITFC between 271-274 ºC, PT between 397- 404 ºC , BTbetween 288-290 ºC.